The Risk Exposures of Asia-focused Hedge Funds - TEO, Melvyn (Institutional Knowledge at Singapore Management University, 2011)
How have Asia-focused hedge funds adjusted their risk exposures in response to the recent financial crisis? By evaluating fund performance relative to an augmented Fung and Hsieh (2004) model, we find that Asia-focused hedge funds have broadly trimmed risk exposures post-crisis. They have reduced their exposure to small stocks relative to large stocks, scaled back their loadings on high yield corporate bonds relative to low yield U.S. sovereign debt, and pared their allocation to the Japanese equity markets. At the same time, however, they are now more exposed to Asian equity markets.